INFLUENCE OF POLYMER SURFACES ON BACTERIAL BIOFILM FORMATION - Sanni, Olutoba (2020)
High throughput materials discovery screens have revealed polymers that reduce bacterial surface colonization which have progressed to ongoing clinical trials [Hook et al. Nature Biotech 2012]. These novel poly(meth)acrylate coatings reduced biofilm formation by Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli in laboratory cultures in vitro and in vivo in a mouse foreign body infection model. These coatings are known to function by preventing biofilm formation; however, why the bacterial cells respond in this way to these polymers has yet to be elucidated. This knowledge gap leaves us unable to undertake rational design of novel materials to prevent bacteria attachment. In this thesis, we focus on understanding the influence of the polymer surface on attachment of bacteria and subsequent biofilm formation.